2017
DOI: 10.1080/1750399x.2017.1344816
|View full text |Cite
|
Sign up to set email alerts
|

Addressing employability and enterprise responsibilities in the translation curriculum

Abstract: This paper discusses 'employability' in Translation Studies in the UK. After a review of current practice and developments, I suggest an adapted working framework that can be applied by Translation and Interpreting Higher Education Institutions (HEIs). I will argue that no single prescribed model can be applied to all institutions but that a holistic and collaborative approach is needed for a realistic implementation of employability practices in the curriculum.The context of the research on which the paper is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…Authors such as Vandepitte (2009), Calvo et al (2010, Thelen (2016) or Galán-Mañas (2017, among others, argue that the competences needed for employability can be summed up in two key concepts: entrepreneurial competence and interpersonal competence. However, an increasing number of scholars (Pym 2005;Kelly 2007;Morón 2016;Morón/Medina 2016;Calvo 2017;Rodríguez 2017;etc.) also highlight the need to focus on cross-disciplinary competences and to identify new professional profiles so as to make Translation Studies more flexible. The idea is to foster the students' ability to develop the new skills they may need in a constantly changing labour market (Montalt 2011; European Ministers Responsible for Higher Education 2015).…”
Section: Specialisation and Employability In Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors such as Vandepitte (2009), Calvo et al (2010, Thelen (2016) or Galán-Mañas (2017, among others, argue that the competences needed for employability can be summed up in two key concepts: entrepreneurial competence and interpersonal competence. However, an increasing number of scholars (Pym 2005;Kelly 2007;Morón 2016;Morón/Medina 2016;Calvo 2017;Rodríguez 2017;etc.) also highlight the need to focus on cross-disciplinary competences and to identify new professional profiles so as to make Translation Studies more flexible. The idea is to foster the students' ability to develop the new skills they may need in a constantly changing labour market (Montalt 2011; European Ministers Responsible for Higher Education 2015).…”
Section: Specialisation and Employability In Translationmentioning
confidence: 99%
“…
The current increase of automation (Rodríguez 2017;Massey/Wieder 2018) and the emergence of new needs and forms of communication are triggering substantial changes in the translation profession, in the role of the translator and in translator education. Previous studies (Muñoz-Miquel 2014 have shown the rich variety of tasksbeyond those traditionally considered -that medical translators perform in the workplace, including heterofunctional translation, editing, or community management.
…”
mentioning
confidence: 99%
“…However, these are limited, since they do not include most of the issues identified in Table 1. Despite the fact that entrepreneurial competence as such does not seem to have a space 'of its own' in the main TC models, an increasing number of studies address employability with a view to fostering entrepreneurship among students (Vandepitte 2009, Chouc/Calvo 2010, Thelen 2016, Way 2016, Calvo 2017, Rodríguez 2017, Galán-Mañas 2017. These works refer mainly to initiatives of a curricular or extracurricular nature, such as internships, real translation assignments and professional tasks, seminars by professionals and career fairs.…”
Section: Entrepreneurial Competence and Versatility In Timentioning
confidence: 99%
“…In line with this view, with reference to Spain, an increasing number of authors criticise the excessive rigidity of the profiles proposed in the White Paper on the TI Degree 1 and advocate fostering transversal competences to be able to respond to emerging and diverse professional tasks (Pym 2005, Kelly 2007, Morón/Medina 2016, Calvo 2017, Rodríguez 2017.…”
Section: Entrepreneurial Competence and Versatility In Timentioning
confidence: 99%
See 1 more Smart Citation